GAMBARAN EPIDEMIOLOGI KEJADIAN CAMPAK DI KABUPATEN BADUNG PROVINSI BALI TAHUN 2014-2019 - Riastini, Ni Made Rai; Sutarga, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021DO - 10.24843/ACH.2021.v08.i01.p12, 2021)
ABSTRACT Meales Surveillance annually report more than 11,000 suspected cases of measles in Indonesia. There are  a lot of measles suspects were also found in Badung Regency from 2014-2019. Starting at 499 suspected cases in 2014 to only 21 suspected cases in 2019. The purpose of this study was to determine the description epidemiology of measles in Badung Regency in 2014 - 2019. The type of this research is descriptive epidemiology with cross sectional design. The data source in this study is from Case Based Measles Surveillance Badung Regency Health Office in 2014-2019. The results showed that the incidence of measles in 2014-2019 tended to decrease with the highest incidence in 2014 and the lowest in 2019. The highest incidence of measles in Badung Regency occurred in South Kuta District. For the period 2014-2019, the highest incidence of measles was in the 5-9 years age group and was dominated by male. An interesting phenomenon was founded that the incidence of measles is more common in patients with immunized status. The advice given to the Badung District Health Office to carry out a MR immunization campaign again to increase the formation of community immunity. Keywords : Epidemiology, Measles, Surveillance